THE RELATIONSHIP BETWEEN MATERNAL CHARACTERISTICS AND CULTURAL PATTERNS OF TODDLER FEEDING WITH THE INCIDENCE OF STUNTING : A CROSS-SECTIONAL STUDY - Desi Ratnasari; Sri Oktavia; Retno Anggraeni Puspita; Yulidian Nurpratiwi (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Growth, cognitive development, and children's health are all impacted by Stunting (WHO, 2020).  Maternal education, socioeconomic status, and eating habits can all contribute to Stunting (UNICEF, 2020).  The prevalence of Stunting in Indonesia was 24.4%; in Bekasi Regency, it was 21.5% in 2021 and dropped to 13.8% in 2023 (Ministry of Health of the Republic of Indonesia, 2023).  The purpose of this study is to examine the connection between the frequency of Stunting at Sentra Medika Cikarang Hospital in Bekasi Regency and maternal traits and cultural toddler feeding practices.  From a population of 75 people and sampling using purposive sampling technique, 43 mothers with stunted children were obtained. Data was collected through a structured questionnaire and processed using the chi-square test to analyze the relationship between variables. The results of the study showed that there was a significant relationship between maternal characteristics, such as education level and socioeconomic status, with the incidence of Stunting (p = 0.013). In addition, the culture of feeding patterns was also related to the incidence of Stunting (p = 0.024). Maternal characteristics and culture of feeding patterns play a role in the incidence of Stunting. Therefore, education regarding feeding patterns needs to be improved to prevent Stunting.